Kesesuaian Lokasi untuk Pengembangan Green-Blue Open Space di Kawasan Pesisir Kota Makassar - Musdalifah Musdalifah; Slamet Trisutomo; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Sustainability emerged as the most influential paradigm in managing and planning coastal area. One of the effort in realizing sustainability in the coastal area is by developing public space such as Green-Blue Open Space (GBOS), in view of the role GBOS that have a great impact in improving quality of life, aesthetics, environmental health, economic growth, city vitality, and contributing to increase disaster resilience. Meanwhile, Makassar City faced the issue about lack of availability of Green Open Space that only rich 7,3% and also the issue of sea level rise in the coastal area that will increase in the future. Researcher is interested in analyzing the level of suitability of the location to developt GBOS in coastal area of Makassar City based on GBOS theory and principle. Location of this study included 25 subdistrict in coastal area of Makassar City. The research method use the scoring and overlay method of location suitability criteria in develop GBOS using the Arc GIS application. The result of this study indicates 2 subdistrict that have the most suitable level of location suitability that are Ende and Pattunuang Subdistrict, 8 subdistrict in suitable level, 10 subdistrict in less suitable level, and 5 subdistrict in not suitable level.